BASIC CONDITIONS FOR OPERATION INCREASE OF EFFECIENCY AND QUALITY OF THE MARINE EQUIPMENT - V. P. Semenov (Дискурс, 2016)
In the article the basic conditions for effective and high-quality operation of marine equipment, as well as a number of modern ways to improve quality management, organized on the principles of total quality management are considered.